2022
DOI: 10.1097/md.0000000000028434
|View full text |Cite
|
Sign up to set email alerts
|

Fetal intracranial hemorrhage and maternal vitamin K deficiency induced by total parenteral nutrition

Abstract: Rationale: Fetal brain hemorrhage is rare. It is caused mainly by maternal trauma or fetal coagulation disorder, but in some cases, vitamin K deficiency may be the cause. Patient concerns: We describe the case of a pregnant woman with bowel obstruction who was susceptible to vitamin K deficiency due to oral diet restriction, decreased intestinal absorption, and limited intravenous vitamin K supplementation. Diagnosis: After 18 days of intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…After appropriate counselling, patients who require TPN during conservative management for SBIO should be referred to experienced obstetric centres where TPN and careful monitoring of the maternal and foetal conditions can be carried out. In an unfortunate case, Lee S et al reported a case where the patient presented with SBIO secondary to adhesions in the second trimester [ 33 ]. The patient was started on TPN and observed closely for 18 days.…”
Section: Discussionmentioning
confidence: 99%
“…After appropriate counselling, patients who require TPN during conservative management for SBIO should be referred to experienced obstetric centres where TPN and careful monitoring of the maternal and foetal conditions can be carried out. In an unfortunate case, Lee S et al reported a case where the patient presented with SBIO secondary to adhesions in the second trimester [ 33 ]. The patient was started on TPN and observed closely for 18 days.…”
Section: Discussionmentioning
confidence: 99%
“…In our study no higher rates of hematochezia, diarrhea, and anastomotic leakage were associated with EOF, which indicated good tolerance of EOF in infants who underwent an IA. Postoperative DOF further aggravates nutrient consumption and insulin resistance, which results in impaired immune function, delayed wound healing, decreased muscle strength, and increased complications ( 16 ), and is primarily associated with delayed gut development and metabolic diseases in neonates and infants ( 21 , 22 ). EOF can stimulate the secretion of digestive juices, which may enhance the recovery of intestinal function ( 7 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study the hospital stay was shortened by EOF for infants who underwent an IA, which may be attributed to the decreased use of PN. As a result of the rapid growth and development of infants, DOF or increasing the usage of PN delays gut development, reduced the regeneration of intestinal mucosal epithelial cells, and increased apoptosis, thus leading to mucosal atrophy, barrier function impairment, and eventually intestinal bacterial translocation and sepsis ( 21 , 39 ); however, EOF has been shown to be beneficial in gut development, regeneration of the intestinal mucosal epithelium, maintenance of the integrity of the gut barrier, and prevention of bacterial translocation ( 43 , 44 ), which promotes the recovery of intestinal function. These findings indicate that EOF following an IA is effective in infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation